2016
DOI: 10.1002/jcp.25312
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Stiffness Controls VEGF Signaling and Processing in Endothelial Cells

Abstract: Vascular endothelial growth factor A (VEGF) drives endothelial cell maintenance and angiogenesis. Endothelial cell behavior is altered by the stiffness of the substrate the cells are attached to suggesting that VEGF activity might be influenced by the mechanical cellular environment. We hypothesized that extracellular matrix (ECM) stiffness modifies VEGF-cell-matrix tethering leading to altered VEGF processing and signaling. We analyzed VEGF binding, internalization, and signaling as a function of substrate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 58 publications
(116 reference statements)
3
50
1
Order By: Relevance
“…However, others have observed decreased VEGFR-2 internalization in bovine aortic endothelial cells cultured on compliant substrates [37]. Strikingly, this study observed reduced β1 integrin activation with increasing matrix stiffness, whereas many others report heightened integrin activation and signaling as a function of ECM stiffness [10,14,42,64], which could contribute to the differences in results.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…However, others have observed decreased VEGFR-2 internalization in bovine aortic endothelial cells cultured on compliant substrates [37]. Strikingly, this study observed reduced β1 integrin activation with increasing matrix stiffness, whereas many others report heightened integrin activation and signaling as a function of ECM stiffness [10,14,42,64], which could contribute to the differences in results.…”
Section: Discussioncontrasting
confidence: 61%
“…While some have begun to delineate the pathways of these chemical and mechanical cues and identify crosstalk mechanisms [3037], most are not yet fully understood. Here, the combined effects of matrix rigidity and VEGF stimulation on endothelial cell behavior were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, elevated Hif1-α levels may contribute to the increased VEGF expression, resulting in up-regulation of ECM components in Antxr1 deficient fibroblasts. Such regulatory effects of VEGF on collagen production are consistent with previous reports demonstrating a striking inductive effect of VEGF on collagen expression in cultured fibroblasts and in skin fibrosis [1922]. It was also shown that VEGF induces fibronectin secretion in human airway smooth muscle cells in an ERK1/2 dependent manner [32].…”
Section: Resultssupporting
confidence: 91%
“…High levels of VEGF were shown to aggravate fibrosis in experimental animal models and stimulate collagen production by cultured fibroblasts isolated from the skin in patients with systemic sclerosis [1922]. To ascertain potential signaling pathways involved in cell autonomous mechanisms of Antrx1 -dependent regulation of ECM we asked whether levels of VEGF in fibroblasts are affected by loss of ANTXR1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation